Protein hydrolysate as a functional food for chronic kidney disease - Meilinah Hidayat; Sijani Prahastuti; Andreanus Andaja Soemardji; Mohammad Yusuf; Khomaini Hasan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
No Abstract